(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The concept of Feminism in the Indian context and its leit motif are described while taking stock of the status and significance of feminism in the distant cultural past of India. The researcher has made an attempt to trace the political climate responsible for the resurgence of feminism which has long been stifled In the name of convention and upkeep of tradition. A few women autobiographers of the twentieth century and their reflection on self-worth which is the other name for feminism has been taken into account.